ANALISIS MAQASID AL-SHARI’AH TERHADAP HUKUMAN DISIPLIN BERAT ATAS PELANGGARAN IZIN PERCERAIAN OLEH PEGAWAI NEGERI SIPIL MENURUT PERATURAN PEMERINTAH NOMOR 94 TAHUN 2021 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL - Shafira Candra Dewi; Muhammad Solikhudin; Mochammad Agus Rachmatulloh (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
Abstract: Changes in regulations in Indonesia aim to develop law in accordance with the times. One of the regulations that was changed was the PP on Civil Servant Discipline which was originally regulated by PP No. 53 of 2010 and then replaced by PP No. 94 of 2021. There is an interesting thing found by the author when one of the severe disciplinary penalties in PP No. 53 of 2010 mentions a penalty of